THE HYGIENIC EVALUATION OF THE IMPACT OF SCHOOL SUPPLIES ON THE HEALTH OF CHILDREN AT THE PRIMARY SCHOOL (Journal of Pharmaceutical Negative Results, 2023)
At present time, the problem of heavy school bags (backpacks) represents one of acute problems and thus requires a quick solution. Schoolchildren carry on their backs schoolbags weighing significantly times higher than the permitted orthopedic limits. The problem of the heaviness of schoolbags is not studied well enough in Kazakhstani, CIS area and in the other foreign scientific literature. The consequences of carrying heavy weights can lead to health problems in schoolchildren that can end up with problems starting from low attention and knowledge acquisition and further incorrect bones cultivation. This study was conducted among pupils of the 3rd and 4th forms at educational institutions of the city of Almaty. The weight of schoolbags with school supplies was measured daily during the working week in winter and in summer.